LINGKUNGAN TEMPAT TINGGAL DAN HUBUNGANNYA DENGAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR NEGERI 03 LANGKI KECAMATAN TANJUNG GADANG KABUPATEN SIJUNJUNG - Dini Susanti; Rosi Anggraini (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This research is motivated by observations made at SD Negeri 03 Langki, Tanjung Gadang District, Sijunjung Regency. The purpose of this study was to study the description of the environment where students live as well as to learn how to study students in SD Negeri 03 Langki Subdistrict of Tanjung Gadang, Sijunjung District, to find out the relationship between the environment of educators' residence and learning participants at SD Negeri 03 Langki Subdistrict of Tanjung Gadang, Sijunjung District . This study uses quantitative methods with correlational types, 144 study populations and 38 samples of this study are research samples because of more than 100 people. The technique of collecting data in this research uses a questionnaire, after the data is obtained the researcher analyzes the data with the formula of percentage and moment of production. The results in this study are: (1) The environment of residence in SD 03 Langki Subdistrict of Tanjung Gadang Sijunjung Regency is classified as good (2) the learning motivation of students at SD Negeri 03 Langki Subdistrict of Tanjung Gadang Sijunjung Regency is classified as low (3) between the Neighborhood of residence with learning motivation of students in SD Negeri 03 Langki, Tanjung Gadang District, Sijunjung Regency. Researchers suggest after conducting research on equal participation between schools and the community in increasing students' learning motivation. Keywords: Living Environment, Student's Learning Motivation